2012
DOI: 10.1210/er.2010-0028
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity in Developing Countries: Epidemiology, Determinants, and Prevention

Abstract: Rapidly changing dietary practices and a sedentary lifestyle have led to increasing prevalence of childhood obesity (5-19 yr) in developing countries recently: 41.8% in Mexico, 22.1% in Brazil, 22.0% in India, and 19.3% in Argentina. Moreover, secular trends indicate increasing prevalence rates in these countries: 4.1 to 13.9% in Brazil during 1974-1997, 12.2 to 15.6% in Thailand during 1991-1993, and 9.8 to 11.7% in India during 2006-2009. Important determinants of childhood obesity include high socioeconomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
446
6
60

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(534 citation statements)
references
References 121 publications
22
446
6
60
Order By: Relevance
“…29,30 A possible explanation for these results might be that obesity in Latin American countries is related to high socioeconomic status. 40 Thus, despite the inappropriate nutritional status, the children with access to better education might present more positive oral health behaviors, including oral hygiene habits, leading to overall lower caries occurrence in this population group.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 A possible explanation for these results might be that obesity in Latin American countries is related to high socioeconomic status. 40 Thus, despite the inappropriate nutritional status, the children with access to better education might present more positive oral health behaviors, including oral hygiene habits, leading to overall lower caries occurrence in this population group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the associations between SES and childhood overweight and obesity vary between countries with different wealth characteristics [11,12] . These studies suggest that in countries with higher income, 2 childhood overweight and obesity are associated with lower SES [8,12,13] , while in poorer countries childhood overweight and obesity is associated with higher SES levels [5,12,14] . In order to further understand the socioeconomic factors affecting overweight and obesity, studies looked at inequalities within countries.…”
Section: Introductionmentioning
confidence: 95%
“…Until recently, high rates of childhood overweight/ obesity were observed mainly in developed countries, with an average prevalence of above 20% in the Americas and Europe, compared to less than 10% in Africa and Asia [4] . However, recent studies illustrate an increase in prevalence of childhood overweight and obesity in developing regions, such as Africa and Asia [5,6] , while in developed regions childhood overweight/ obesity begins to reach a plateau (mostly in the US, Europe and Oceania) [7,8] . In recent years, a growing body of literature has been emphasizing the impact of community and environmental factors on childhood obesity [9,10] , beyond the effect of individual characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…16 Birth weight was categorized as low birth weight (less than 2,500 g), normal (2,500-4,000 g) or high birth weight (more than 4,000 g).…”
Section: Physical Examination and Biochemical Measurementsmentioning
confidence: 99%